Staging Parkinson's Disease Combining Motor and Nonmotor Symptoms Correlates with Disability and Quality of Life. (15th May 2021) - Santos García, D.; De Deus Fonticoba, T.; Paz González, J. M.; Cores Bartolomé, C.; Valdés Aymerich, L.; Muñoz Enríquez, J. G.; Suárez, E.; Jesús, S.; Aguilar, M.; Pastor, P.; Planellas, L. L.; Cosgaya, M.; et al.
Abstract : Introduction . In a degenerative disorder such as Parkinson's disease (PD), it is important to establish clinical stages that allow to know the course of the disease. Our aim was to analyze whether a scale combining Hoehn and Yahr's motor stage (H&Y) and the nonmotor symptoms burden (NMSB) (assessed by the nonmotor symptoms scale (NMSS)) provides information about the disability and the patient's quality of life (QoL) with regard to a defined clinical stage. Materials and Methods . Cross-sectional study in which 603 PD patients from the COPPADIS cohort were classified according to H&Y (1, stage I; 2, stage II; 3, stage III; 4, stage IV/V) and NMSB (A: NMSS = 0–20; B: NMSS = 21–40; C: NMSS = 41–70; D: NMSS ≥ 71) in 16 stages (HY.NMSB, from 1A to 4D). QoL was assessed with the PDQ-39SI, PQ-10, and EUROHIS-QOL8 and disability with the Schwab&England ADL (Activities of Daily Living) scale. Results . A worse QoL and greater disability were observed at a higher stage of H&Y and NMSB (p < 0.0001 ). Combining both (HY.NMSB), patients in stages 1C and 1D and 2C and 2D had significantly worse QoL and/or less autonomy for ADL than those in stages 2A and 2B and 3A and 3B, respectively (p < 0.005 ; e.g., PDQ-39SI in 1D [ n  = 15] vs 2A [ n  = 101]: 28.6 ± 17.1 vs 7.9 ± 5.8; p < 0.0001 ). Conclusion . The HY.NMSB scale is simple and reflects the degree of patient involvement more accurately than the H&Y. Patients with a lower H&Y stage may be more affected if they have a greater NMS burden.